Sosialisasi Usaha Mikro Kecil dan Menengah (UMKM) Dalam Produk Keripik Singkong Sebagai Upaya Menjadi Produk Unggulan Di Desa Tanjung Ibus - Muhammad Zihanuddin; Nur Haliza; Aprisa Aulia Saputri; Yusuf Abdullah; Novira Arafah (peduli riset dan pengabdian masyarakat, 2024)
The activity of making cassava chips is one of the efforts to make cassava chips a superior MSME product in Tanjung Ibus Village. The aim of this activity is to provide an understanding of how to make cassava chips properly and correctly to the people of Tanjung Ibus and to provide training to the community in improving the community's MSMEs. The method of implementing this activity is through socialization, providing materials and direct practice in making cassava chips. The results of the discussion show that the socialization of Micro, Small and Medium Enterprises (MSMEs) in cassava chips products as an effort to become a superior product in Tanjung Ibus Village provides benefits in the form of new learning for the people of Tanjung Ibus Village. The community was guided directly by Abangda Rahman and KKN student STAI Jam'iyah Mahmudiyah Tanjung Pura during the socialization process. Through this activity, the community in Tanjung Ibus Village can feel the benefits of this activity and it is hoped that they will be encouraged to continue to develop themselves and can make cassava chips a superior MSME product in Tanjung Ibus Village.